2015
DOI: 10.1186/s13000-015-0297-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on expression of lncRNA RGMB-AS1 and repulsive guidance molecule b in non-small cell lung cancer

Abstract: BackgroundThe relationships between lncRNAs and tumors have currently become one of the focuses on cancer studies. However, there are a few studies about lncRNAs in non-small cell lung cancer (NSCLC) at present.MethodsMicroarray analysis was designed to study the expression patterns of lncRNAs in three pairs of NSCLC tissues. The expression of lncRNA RGMB-AS1 and repulsive guidance molecule b (RGMB) were detected in 72 paired NSCLC tissues and adjacent normal tissues by qRT-PCR assay. The relations of lncRNA R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The Kaplan-Meier analysis showed FENDRR was a prognostic biomarker of overall survival for NSCLC patients, which corresponded to Xu's et al report in gastric cancer [8]. Recent studies showed that several lncRNAs, including HMlincRNA717 and RGMB-AS1 [20,21], were associated with overall survival of NSCLC patients, and could be prognostic factors for patients with NSCLC. Further penetrating research might provide a diagnosis target and prognostic biomarker for NSCLC.…”
Section: Discussionsupporting
confidence: 72%
“…The Kaplan-Meier analysis showed FENDRR was a prognostic biomarker of overall survival for NSCLC patients, which corresponded to Xu's et al report in gastric cancer [8]. Recent studies showed that several lncRNAs, including HMlincRNA717 and RGMB-AS1 [20,21], were associated with overall survival of NSCLC patients, and could be prognostic factors for patients with NSCLC. Further penetrating research might provide a diagnosis target and prognostic biomarker for NSCLC.…”
Section: Discussionsupporting
confidence: 72%
“…Our microarray data analysis revealed that the XLOC_008466 level was up-regulated in NSCLC tissues [13]. In this study, we further verified the expression of XLOC_008466 in 63 NSCLC patients and analyzed its expression features in the patient clinicopathological characteristics.…”
Section: Resultsmentioning
confidence: 91%
“…Based on our previous microarray data analysis of lncRNAs in NSCLC tissues [13], our present study was performed to confirm the expression of XLOC_008466 and explore the potential regulatory network of XLOC_008466-miRNA-mRNA using bioinformatics prediction and sequence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…1B, Supplementary Table S1). In addition to the selected lncRNAs, we chose 18 well characterized lncRNAs associated with the occurrence and development of NSCLC as positive controls [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] ( Supplementary Table S1).…”
Section: Repurposing Microarray Data For Lncrna Selection In Nsclcmentioning
confidence: 99%